2016
DOI: 10.1016/j.nbd.2016.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic administration of the p53 inactivator pifithrin-α oxygen analogue reduces hippocampal neuronal loss and improves cognitive deficits after experimental traumatic brain injury

Abstract: Traumatic brain injury (TBI) is a major cause of death and disability worldwide. Neuronal apoptosis in the hippocampus has been detected after TBI. The hippocampal dysfunction may result in cognitive deficits in learning, memory, and spatial information processing. Our previous studies demonstrated that a p53 inhibitor, pifithrin-α oxygen analogue (PFT-α (O)), significantly reduced cortical cell death, which is substantial following controlled cortical impact (CCI) TBI, and improved neurological functional out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 82 publications
3
40
0
1
Order By: Relevance
“…Although best known as a tumor suppressor induced by DNA damage, several studies have documented p53 induction in patient tissue and in experimental models of a variety of chronic and acute neurodegenerative disorders (Culmsee and Mattson, 2005), which include Alzheimer's disease (de la Monte et al, 1997; Kitamura et al, 1997), Huntington’s disease (Bae et al, 2005), Parkinson's disease (Duan et al, 2002; Mogi et al, 2007; Qi et al, 2016), ALS (Martin, 2000; Ranganathan and Bowser, 2010) and traumatic brain injury (Yang et al, 2016). Interestingly, our results demonstrate that induction and nuclear accumulation of p53 are not sufficient to drive neurodegeneration in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Although best known as a tumor suppressor induced by DNA damage, several studies have documented p53 induction in patient tissue and in experimental models of a variety of chronic and acute neurodegenerative disorders (Culmsee and Mattson, 2005), which include Alzheimer's disease (de la Monte et al, 1997; Kitamura et al, 1997), Huntington’s disease (Bae et al, 2005), Parkinson's disease (Duan et al, 2002; Mogi et al, 2007; Qi et al, 2016), ALS (Martin, 2000; Ranganathan and Bowser, 2010) and traumatic brain injury (Yang et al, 2016). Interestingly, our results demonstrate that induction and nuclear accumulation of p53 are not sufficient to drive neurodegeneration in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…The study on the role of SiO 2 in lung fibroblasts revealed that SiO 2 can induce pulmonary fibrosis, which is mediated by an increased expression of p53 and PUMA in cells. However, the activation and migration of SiO 2 ‐induced fibroblasts were antagonized after silencing p53 with p53 siRNA . The mRNA expression of p53 and the protein expression of PUMA were significantly increased in HepG2 cells after being treated with MC‐LR for 24 hours .…”
Section: Discussionmentioning
confidence: 96%
“…However, the activation and migration of SiO 2 -induced fibroblasts were antagonized after silencing p53 with p53 siRNA. 40,41 The mRNA expression of p53 and the protein expression of PUMA were significantly increased in HepG2 cells after being treated with MC-LR for 24 hours. 42 In addition, the study of zebrafish embryotoxicity induced by MC-LR also showed that MC-LR can induce a significant increase in the expression of p53 and bax protein in zebrafish embryos, suggesting that the p53-Bax-Bcl-2 pathway plays an important role in the MC-LR-induced embryotoxicity of zebrafish.…”
Section: Effect Of Pft-α On the Expression Of Apoptosisrelated Protmentioning
confidence: 99%
“…Regardless, it is tempting to speculate that treatments that could relieve telomere dysfunction or abrogate the p53 mediated stress response could potentially ameliorate patient outcomes. Pifithrin-α has already been shown to be an effective treatment to restore neuronal function in murine models of injury or stroke 100102 . Significant future effort will be devoted to determining both whether telomere dysfunction is a common trigger for ID Syndromes, and whether telomere restoration could potentially help patients.…”
Section: Discussionmentioning
confidence: 99%